PENGARUH PROMOSI DAN INDEX PRESTASI TERHADAP PENEMPATAN KERJA SERTA DAMPAKNYA PADA PENERIMAAN MAHASISWA BARU DI POLITEKNIK LP3I JAKARTA - Kusmanto Kusmanto (JURNAL LENTERA BISNIS, 2018)
AbstractAcceptance of new students at a college is a very important routine activity whether it is in public or private universities. Especially in private tertiary institutions, as well as the Polytechnic LP3I Jakarta because with the large number of prospective students who enroll or choose to go to a college it will determine the life of the college. In this study it was intended to find out how much influence promotion and cumulative achievement index (GPA) had on job placement and its impact on new student admissions. In this study shows that the effect of promotion (X1) on work placement (Y) is 0.366 or 36.6%, while the influence of the cumulative achievement index (GPA) (X2) on work placement (Y) is 0.614 or 61.4%, while the effect of simultaneous (overall) promotion (X1) and cumulative achievement index (GPA) (X2) on work placement (Y) in total is 1.052 (105.2%) which proves that in this study promotion (X1) and achievement index cumulative (GPA) has a large influence on work placements with a total of 105.2%, while the influence of total impact of promotion (X1), cumulative achievement index (GPA) (X2) and work placement (Y) on new student admissions (Z) is 0.948 or 94.8%. Thus clearly promotion, the cumulative achievement index has a large influence on work placements while the impact will affect the acceptance of prospective new students.Keywords: Promotion of Cumulative Achievement Index, Job Placement, New Student Admission, Path Analysis.